Optoelectronic property comparison for isostructural Cu2BaGeSe4 and Cu2BaSnS4 solar absorbers. Issue 41 (13th October 2021) - Kim, Yongshin; Hempel, Hannes; Levcenco, Sergiu; Euvrard, Julie; Bergmann, Eric; Gunawan, Oki; Unold, Thomas; Hill, Ian G.; Mitzi, David B.
Abstract : This study identifies key underlying differences in electronic properties of vacuum-deposited Cu2 BaGeSe4 and Cu2 BaSnS4 thin films. Abstract : To target mitigation of anti-site defect formation in Cu2 ZnSnS4− x Se x, a new class of chalcogenides, for which Ba or Sr (group 2) replace Zn (group 12), has recently been introduced for prospective solar absorber application. Cu2 BaGeSe4 (CBGSe) and Cu2 BaSnS4 (CBTS) are two such compounds, which share a common trigonal crystal structure ( P 31 space group) and similar quasi-direct band gap (∼2 eV). While CBTS-based films have already been studied, there are no reports yet on films and solar cells based on related CBGSe. To identify key differences and similarities in the electronic properties between these two materials, electronic characteristics ( e.g., carrier concentration, mobility, electron affinity, defect levels, recombination, and charge carrier kinetics) of vacuum-deposited CBGSe and CBTS films are compared using a variety of characterization methods. Hall effect measurements reveal that CBGSe films have relatively higher hole carrier concentration and lower mobility (3 × 10 15 cm −3, 0.6 cm 2 V −1 s −1 ) compared to CBTS (5 × 10 12 cm −3, 3.5 cm 2 V −1 s −1 ). Photoelectron spectroscopy yields low electron affinity values for both CBGSe (3.7 eV) and CBTS (3.3 eV), pointing to the necessity of pursuing low electron affinity buffer materials for both types of absorbers. At low temperatures, CBGSe films show free-exciton photoluminescence, as well as pronounced deep-level emission at ∼1.4 eV, while CBTS films exhibit a strong bound-exciton signal with noticeably less intense deep-level emission than for CBGSe. Charge carrier kinetics, transport, and recombination properties of both types of films are also analyzed using optical-pump terahertz-probe spectroscopy and time-resolved microwave conductivity. The first CBGSe prototype solar cells (using chemical bath deposited CdS as a buffer layer) show a maximum of 1.5% efficiency with ∼0.62 V open-circuit voltage. The measured properties point to possible limiting factors for CBGSe and related films for PV and optoelectronics and provide insights on possible approaches for improvement within this multinary chalcogenide family.